Enhanced-Role Based Access Control (E-RBAC) with Trust Factor for Cloud Software- as-a-Service Paradigm - Geetha, N; Anbarasi, MS (International Journal of Computer Sciences and Engineering, 2025)
Software-as-a-Service (SaaS) paradigm is one of the most popular forms of cloud services in today’s multi-tenant technological architecture. The role of multi-tenancy architecture is to offer services to its tenants with customized features of applications they need. Data isolation and resource sharing between multiple tenants in such architecture is more complicated task. Access control models takes accountability of the verification mechanism, the administration and the proper governance of the resources and related services. New architectural model is therefore required to maintain simple relation between the providers and multiple tenants in the system with a strong security feature. SaaS paradigm also needs an effective portability and orchestration mechanism over a virtualized infrastructure. To address these issues, we present a novel architecture called the E-RBAC (Enhanced- Role Based Access Control) model to enhance the security and access control over the services in the SaaS infrastructure by calculating the trust of the roles assigned. We also present a comparative analysis of SaaS provisioning with and without E-RBAC security model.